Human anti-D immunoglobulin preparations: potency standardisation milestones - N. S. Vildanova; E. S. Kormshchikova; E. N. Kalinina; K. A. Vorobiev; I. V. Paramonov; E. Yu. Kudasheva (Биопрепараты: Профилактика, диагностика, лечение)
Human anti-D immunoglobulin preparations derived from human immune plasma are much needed and highly effective for specific anti-D prevention of perinatal complications and treatment of primary immune thrombocytopenia. The effectiveness of immune suppression is a direct function of the active ingredient dose received with the medicinal product. To improve the accuracy of anti-D antibody quantification, it is recommended to use certified reference materials with values assigned in international units (IUs). The aim of this study was to analyse the main stages in the development of the international standards (ISs) for human anti-D immunoglobulin potency testing and to substantiate the need for a national standard for anti-Rho(anti-D) antibody quantification. The article describes the creation of the first and subsequent ISs, the procedure for establishing the IU equivalent for the anti-Rho(anti-D) antibody concentration, the characteristics of the raw materials and preparations used, and the anti-Rho(anti-D) antibody assay methods applied to certify the ISs. According to the study conclusions, it is necessary to develop and certify a national standard for the content of anti-Rho(anti-D) antibodies that will meet the requirements of the corresponding Russian regulations.